A note on a cross-sectional GMM estimator in the presence of an observable common shock. Issue 2 (3rd March 2020) - Khovansky, Serguey; Zhylyevskyy, Oleksandr
Abstract : This paper studies property of a modified GMM estimator employed for a single cross-section of data that are strongly dependent due to an observed stochastic common shock. The estimator is shown to be asymptotically mixed normal. Statistical inference can be conducted with a Wald test. An overidentifying restrictions test is suggested.